Effect of interior changes on earthquake resistance of buildings - case: reinforced concrete frame system - Moosavi, Mahsa Sadat Fard (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
Earthquakes are one of the most disturbing natural hazards which cause enormous life and property losses. However, earthquake engineering has highlighted itself as an interdisciplinary subject over the past few decades. Different professions as seismology, structural and geotechnical engineering, architecture, urban planning, information technology and some of the social sciences, have began to address different characteristic effects on the earthquake resistance of buildings. The purpose of this study is to investigate lack of safety in the event of earthquake occurrence due to interior modification in the buildings during their life cycle. This study investigates the potential problems arising due to improper interior changes, applied on existing structures, and also tries to reveals the importance of careful considerations, before any modification from architectural point of view. This study reviews some background information regarding the issue of earthquake as well as a Turkish seismic design code of practice developed together with an explanation of the so – called “irregular building”. Also two case studies were performed to show the importance of interdisciplinary work of interior architects with civil engineers when performing any change on the building. Keywords: Earthquake Codes, Irregular Building, Interior Modification, Earthquake Architecture

ÖZ: Depremler muazzam can ve mal kaybına yol açabilen sarsıcı doğal felaketlerdendir. Ne var ki, geçtiğimiz birkaç onyılda deprem mühendisliği, disiplinlerarası bir dal olarak kendini göstermeye başladı. Sismoloji, yapı ve jeoteknik mühendisliği, mimarlık, şehircilik, bilgi teknolojileri ve bazı sosyal bilim dalları da yapıların depreme dayanıklılığı ile ilgili farklı konulara dikkat çekmektedirler. Bu çalışmanın amacı, yapıların yaşam süresi boyunca maruz kaldıkları iç-mekan müdahalelerinin bir deprem sırasında yol açabileceği güvenlik sorunlarını araştırmaktır. Bu çalışma, mevcut yapılarda usule uygun yapılmayan iç-mekan müdahalelerinin ortaya çıkarabileceği potansiyel sorunları irdeler ve herhangi bir mimari değişiklikten önce detaylı araştırmalar yapılmasının önemine dikkat çeker. Bu araştırma, depreme dair temel bilgiler ile birlikte Türk deprem yönetmeliği ve düzensiz yapıları konu alan araştırmaları da inceler. Bunlara ek olarak, bir binaya yapısal müdahale sırasında iç-mimarlar ile inşaat mühendislerinin birlikte çalışmasının önemini göstermek amacıyla iki vaka incelemesi gerçekleştirilmiştir. Anahtar Kelimeler: Deprem Yönetmelikleri, Düzensiz Yapılar, İç Mekan Müdahaleleri, Deprem Mimarlığı
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2013. Supervisor: Assoc. Prof. Dr. Yonca Hürol.
Keywords: Architecture; Earthquake engineering - Interior Design - Reinforced concrete construction; Earthquake Codes; Irregular Building; Interior Modification; Earthquake Architecture